The Impact of COVID-19 on Food Security: Ghana in Review - Apaliya, Maurice Tibiru; Kwaw, Emmanuel; Osae, Richard; Alolga, Rapheal Nammahime; Aikins, Augustina Sackle Sackey; Otoo, Gifty Serwaa; Kaburi, Sandra Ama; Lamptey, Francis Padi; Amo-Broni, Celestina (Journal of Food Technology Research, 2022)
Since the outbreak of the COVID-19 pandemic, Ghana has recorded a total of 130, 727 confirmed cases with 1,207 deaths at the time of writing this article. The COVID-19 pandemic has had a significant influence on nations and regions all around the world since it started and Ghana is no exception. This systematic review discusses COVID-19 measures in Ghana, the impact of COVID-19 on the import and export of Agricultural inputs and food, as well as the impact of COVID-19 on local food system actors. In the second part, measures to prevent food insecurity in Ghana during the outbreak of the pandemic, emerging lessons, and building resilience have also been presented. In several production regions, the Ghanaian food system experienced disturbances that resulted in reduced output due to limited labor mobility; nevertheless, these disruptions were minor and did not appear to have a significant impact on production. The COVID-19 epidemic has disrupted food supplies, putting billions of people's food security in jeopardy. According to some estimates, global hunger might treble as a result of food supply disruptions, especially in poor countries around the world. Ghana's economy is beginning to recover from the effects of the COVID-19 pandemic, and in order to maintain this recovery, the government will need to continue to support both the productive and vulnerable sectors of the economy. Finally, there has never been a better time to eat more of what we grow and to grow more of what we eat than right now.